Kesejahteraan Siswa: Faktor Pendukung dan Penghambatnya - Ana Ianah; Rena Latifa; Risatianti Kolopaking; Muhamad Nanang Suprayogi (Bina Nusantara University, 2021)
The efforts to improve student wellbeing are one of the main concerns in the current educational process. There are a lot of research on wellbeing, but there is still very little research on the wellbeing of children and adolescents, especially in the school context. This paper aims to examine internal and external factors for improving student wellbeing, as well as to reveal the inhibiting factors for student wellbeing. The student wellbeing during childhood and adolescence is important because it will determine the quality of life of students in the future. The results of the study show the factors of increasing wellbeing internally are: 1. The ability to adapt; 2. Learning orientation; 3. Self-assessment; 4. Personal characteristics, while external factors are 1. Student teacher relations; 2. Relationship between children and parents; 3. Friend relations; 4. An environment that supports discipline. While the factors that inhibit wellbeing internally are: 1. Physical health, 2. Students are not maximal in learning, 3. Inadequate achievement, 4. Inadequate material needs, 5. Negative behavior, such as lazy, arrogant, shy, and naughty. While externally are 1. The unpleasant environment 2. Receiving less pleasant treatment; 3. Not able to actualize well.